Recurrent lupus miliaris disseminatus faciei: a case report - Zonunsanga; AK Khare; Manisha; Poonam Saini (Our Dermatology Online, 2015)
Lupus miliaris disseminatus faciei (LMDF) is a granulomatous eruption characterized by monomorphic, reddishbrown papules and nodules predominantly localized on the face. A 43 years old lady presented with multiple, painful, papulo-pustules over face 6 years back. Biopsy showed showed large foci of suppurative granulomatous dermatitis with a large central area of suppuration surrounded by histiocytes and occasional giant cells. Epidermis is not disrupted. Perifollicular and perivascular lymphocytic infiltrates were also seen. The lesions were healed with atrophic scars. She is now presented with multiple asymptomatic papules over bilateral periorbital regions of the face.